1987
DOI: 10.1172/jci113049
|View full text |Cite
|
Sign up to set email alerts
|

Axial heterogeneity of intracellular pH in rat proximal convoluted tubule.

Abstract: In the proximal convoluted tubule (PT), the HCO3 reabsorptive rate is higher in early (EPS) compared with late proximal segments (LPS). To examine the mechanism of this HCO3 reabsorption profile, intracellular pH (pH) was measured along the superficial PT of the rat under free-flow and stationary microperfusion using the pH-sensitive fluorescence of 4-methylumbelliferone (4MU). With 4MU superfusion, pH1 was found to decline along the PT. Observation with 365-nm excitation revealed that EPS were brightly fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Independently of the precise biophysical mechanism, our results suggest that modulation of ClC‐5 by intracellular pH is physiologically relevant, for example to regulate the degree of endosomal acidification. In this regard, it is interesting to note that transcellular pH gradients have been described in proximal tubule cells (Aw and Jones, 1989), and that it has been reported that intracellular pH progressively declines along the proximal tubule (Pastoriza‐Munoz et al , 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the precise biophysical mechanism, our results suggest that modulation of ClC‐5 by intracellular pH is physiologically relevant, for example to regulate the degree of endosomal acidification. In this regard, it is interesting to note that transcellular pH gradients have been described in proximal tubule cells (Aw and Jones, 1989), and that it has been reported that intracellular pH progressively declines along the proximal tubule (Pastoriza‐Munoz et al , 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that pH has a significant impact on Na ϩ transport efficiency in the PT. Pastoriza-Munoz et al (71) reported a decrease in pH c from the early to the late PT. Our simulations indicate that, at a fixed Q ATP , lowering pH c reduces the pmf; this, in turn, decreases ATP formation and P/O (Fig.…”
Section: F255mentioning
confidence: 95%
“…The development of nontoxic fluorescently labeled probes amenable to visualization in live animals has further enhanced the ability to visualize cellular processes in vivo. For instance: (1) nuclei of intact live kidney cells have been stained with Hoechst 33 342 dye, or propidium iodide to study apoptosis; 6,15 (2) the proximal tubule brush border and endocytic vesicles have been labeled with Texas Red-folate in a study of folate uptake; 16 (3) intracellular pH has been determined with pH indicator probes; 17,18 (4) single nephron glomerular filtration rate has been measured using fluorescein isothiocyanate-inulin or Lucifer yellow; 19 and (5) glomerular permeability, proximal tubule endocytosis, and blood flow rates have been studied with labeled albumin and dextrans. [6][7][8][19][20][21][22][23] All of these fluorescent probes are markers that provide vital information on kidney structure and function in health and disease.…”
Section: Fluorescent Reagentsmentioning
confidence: 99%